Obstructive Sleep Apnea, Hypercoagulability, and the Blood–Brain Barrier - Zolotoff, Cindy (J Clin Med, 2021)
Obstructive sleep apnea (OSA) is characterized by repeated episodes of intermittent hypoxia (IH) and is recognized as an independent risk factor for vascular diseases that are mediated by a multitude of mechanistic pathophysiological cascades including procoagulant factors. The pro-coagulant state contributes to the development of blood clots and to the increase in the permeability of the blood–brain barrier (BBB). Such alteration of BBB may alter brain function and increase the risk of neurodegenerative diseases. We aim to provide a narrative review of the relationship between the hypercoagulable state, observed in OSA and characterized by increased coagulation factor activity, as well as platelet activation, and the underlying neural dysfunction, as related to disruption of the BBB. We aim to provide a critical overview of the existing evidence about the effect of OSA on the coagulation balance (characterized by increased coagulation factor activity and platelet activation) as on the BBB. Then, we will present the emerging data on the effect of BBB disruption on the risk of underlying neural dysfunction. Finally, we will discuss the potential of OSA therapy on the coagulation balance and the improvement of BBB.